Social Networks: A Curse or a Blessing? (A Case Study of Selected Students from Auchi Polytechnic) - Uduiguomen, Usifoh Collins; Agwi, Uche Celestine; Aliu, Nefishetu Faith (Discoveries in Agriculture and Food Sciences, 2014)
This paper presents the findings from an investigation into the question whether a social network is a blessing or a curse. We used a sample population of 320 students at Auchi Polytechnic, Auchi in Edo Sate Nigeria as our case study. This investigation was borne out of the ever-increasing interest that a lot of people are expressing in their fraternity with the various social networks and the obvious opportunities and prospects as well as the virtues and vices these social networks portend. Social networks are like legal tenders; on their own, they are neither good nor bad. What defines them and gives them their characteristics are what a user does with them. A lot of unsavory activities (ranging from fraud, identity theft to outright blackmail) have been known to be carried out using social networks as a platform but in retrospect, varying degrees of positive achievements (such as building of mutually beneficial relationships and ties, reestablishment of lost contacts and effective communication) has also been recorded using social networks. From the investigation that we carried out, it was observe that social network can serve as a blessing and it can also serve as a curse depending on how and what a user use it for.